Pengaruh Digital Marketing terhadap Brand Awareness : Studi Kasus Kandang Ayam Resto - Listiana, Dhea; Dwi, Ira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Nowadays the era of information technology makes many things easy to do in the digital world, including in marketing products and searching for products. Digital marketing can be used as the main option in supporting business activities for business people. Social media is used by consumers to find information about a product that is needed or desired. Accuracy in utilizing digital marketing through social networks (social media) is able to build consumer confidence in the products being marketed. This marketing strategy is also used to build brand awareness among consumers. This study examines the effect of digital marketing on the formation of consumer brand awareness using quantitative and qualitative tests. Quantitative data was collected using a sampling technique where respondents knew and had transacted at the Chicken Coop Restaurant. The data analysis technique in this study used SPSS Version 25 software. Based on the results of a simple linear test analysis, it was found that Digital Marketing had a positive and significant effect on Brand Awareness. Qualitative test by conducting interviews with six respondents, it was concluded that digital marketing has an influence on brand awareness.